Comparison Between Apple and Samsung Products Based on Literature - Riyan Yusianto; Qonitah Lutfatullaili (Journal of International Conference Proceedings (JICP), 2018)
This paper aims to know the comparison between Apple and Samsung. The background of this paper is because the competition of both products is very tight. Though this paper will review the features up to the supply chain of both products. The purpose of this study is to find out what is in the Apple and Samsung products in the competition to maintain the product. This study uses secondary data from the existing literature. In addition, also take the results of surveys that have been done in several countries that use both products. keywords : Apple and Samsung, comparison, competition